Laryngoscopy Grade Improvement and Difficult Airway Resolution in Infants With Robin Sequence Undergoing Mandibular Distraction Osteogenesis: A Multi-Institutional Study. (July 2021) - Siegel, Nicholas; Lopez, Joseph; Shi, Aria C.; Neimanis, Sara; Jodeh, Diana; Khavanin, Nima; Redett, Richard J.; Sterni, Laura M.; Walsh, Jonathan M.; Dalesio, Nicholas M.; Rottgers, S. Alex; Morrison, Clinton S.; et al.
Objective: Mandibular distraction osteogenesis (MDO) aims to relieve tongue-based airway obstruction in Robin Sequence (RS). We investigated direct laryngoscopy grade (DLG) improvement and difficult airway (DA) resolution following MDO. Design: Retrospective cohort analysis. Setting: Three tertiary care institutions. Patients: Sixty-four infants with RS who underwent a single MDO procedure in their first year of life were identified from January 2010 to January 2019. Main Outcome Measures: The primary outcome was DLG pre- and post-MDO. Secondary outcomes included DA designation, pre- and post-MDO polysomnographic assessment for obstructive sleep apnea (OSA), length of stay, need for gastrostomy, and major/minor adverse events. Results: Median DLG improved from II pre-MDO to I at the time of distractor removal (n = 43, P < .001). No significant change was seen in patients with a third recorded time point (eg, palatoplasty; n = 78, P = .52). Twenty-six (47%) of 55 patients were designated as DA pre-MDO, and 10 (18%) of 55 patients retained the label post-MDO ( P < .01). Five (50%) of these 10 patients appeared to be inappropriately retained. Median obstructive apnea–hypopnea index improved from 38.6 (range 31.2-62.8) pre-MDO to 2.9 (range 1-3.9) post-MDO (n = 12; P = .002). Conclusion: Mandibular distraction osteogenesis allowed for DLG improvement that was stably maintained as well as functional improvement in OSA, with minimal morbidity. Difficult airway designation persisted in the electronic record of some infants despite clinical resolution.